Experimental study of the acoustical performance of a sonic crystal window in a reverberant sound field. Issue 1 (March 2017) - Lee, Hsiao Mun; Tan, Long Bin; Lim, Kian Meng; Lee, Heow Pueh
The main objective of this study is to establish an innovative solution with the use of sonic crystal window which will ensure a good balance of natural daylighting, noise mitigation, and natural ventilation. Experimental method was used to study the effects of receiver position, angle of louver blade, noise source position, noise divergence, receiver height, and jagged edge on the acoustical performance of a sonic crystal window which was placed between two reverberant rooms. For the first set of experiment, the maximum insertion loss can be found at frequency of 1100 Hz which was about 7.7 dBA. The effects of louver blade angles were reduced with the increasing distance from the sonic crystal window. The amount of noise attenuated by the sonic crystal window was increased by 0.3 dBA when the noise source was located at 2 m away from the sonic crystal window. By comparing with louver blade without jagged edge, the amount of noise attenuated by the sonic crystal window was increased by 0.3 dBA for blade angles of 0° and 30° and 0.1 dBA for blade angle of 60° when the edge of louver blade was in jagged shape.